A preliminary study of comparative and evaluative questions for business intelligence - Lim, Nathalie Rose T. (Animo Repository, 2009)
Comparative and evaluative question answering (QA) systems provide objective answers to questions that involve comparisons and evaluations based on a quantifiable set of criteria. As evaluations involve inferences and computations, answers are not lifted from source text. This entails the need for correct semantic interpretation of comparative expressions, converting them to quantifiable criteria before data can be obtained from source text, processing these information, and formulating natural language answers from the result of the processing. As business intelligence (BI) requires comparisons and interpretations of seemingly unrelated facts, a QA system for this domain would be beneficial. This paper presents a study of some comparative and evaluative questions that are raised in the domain of business intelligence. How these questions are processed is also discussed. © 2009 IEEE.